Agrarian Conflicts Across Ugandan Societies: A Complex Struggle - Asad, Shibli Jamal Shariff; Anshari, Andry; Mulabbi, Andrew (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2024)
Agrarian conflicts in Uganda are deeply embedded in the nation's historical, social, and economic contexts. Rooted in colonial-era land policies, such as the Mailo land system, these conflicts continue to shape land ownership and agricultural practices, contributing to socio-economic inequalities. This paper examines the causes and consequences of agrarian disputes in Uganda, focusing on land tenure disputes, ethnic and regional conflicts, government policies, population pressures, and the commercialization of agriculture. The study finds that historical land tenure systems, particularly the Mailo system, have created lasting inequalities, while modern governmental policies and population growth exacerbate land-related conflicts. Additionally, the shift towards large-scale commercial agriculture has marginalized smallholder farmers, contributing to social instability. Addressing Uganda’s agrarian conflicts requires a comprehensive and inclusive approach to land reform, incorporating stronger governance, sustainable land management, and respect for indigenous rights.